Improving the Quality of Public Services through Training Evaluation with the Kirkpatrick Method - Pryo Handoko; Mohammad Raudy Gathmyr; Mara Elaiza Augustine Flores; Aqila Hj Zaini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to answer the question of how to improve the quality of public service through training and how to evaluate the training to be effective through the Kirkpatrick method. This is qualitative research with a case study approach. Data was collected through unstructured interviews with 30 visitors who are taxpayers to obtain data related to the quality of services provided by civil servants at KPP Pratama Tanah Abang Dua.In addition, to obtain data related to the quality of training held for the civil servants (ASN), the researchers interviewed 10 ASN who had attended the training. The results of this study indicate that the public services implemented at the KPP Pratama Tanah Abang Dua still need to be improved. The services provided by the civil servants are still complained by taxpayers, namely in the aspects of Reliability, Responsiveness, Assurance, Empathy, and Tangible. The results of this study also indicate that the quality of the training that has been held must be improved regarding all aspects of the training, namely the quality of the trainers, the material presented, the type of exercise, case studies and various teaching aids. The training must also be followed up with training evaluations and assessments of all civil servants after participating in the training.